Flag Day - Smith (The February Journal, 2023)
On the 22nd of August 2022, almost six months after ‘the special operation’ in Ukraine began, a National Flag Day concert was staged in Saint Isaac’s Square in Saint Petersburg, featuring TV-style comperes (‘This is our Russia! This is our story! Tell it to your children!’), singers, dancers, and synchronized flag wavers. The only thing missing was an audience. Because most of Saint Petersburg had, for whatever reason, chosen to absent itself from the celebrations, there was no clapping at the concert, no cheering, and no response to the comperes’ vivid injunctions to participate in their version of Russia’s national story. This project consists of a short introductory essay on the relationship between silence and resistance and a photographic account of what happened when a fictional young woman decided to conspicuously resist the comperes’ injunctions by turning her back on Saint Petersburg’s 2022 National Flag Day celebrations.